Women, political empowerment, and decision-making. - CENWOR (Organization : Sri Lanka) ([Colombo?] : Centre for Women's Research, 1995)
Study constitutes part of a program to improve the quality of life of women in Sri Lanka.
"Study funded by Asia Foundation."
Keywords: Women -- Political activity -- Sri Lanka; Women in development -- Sri Lanka; Sri Lanka -- Politics and government